KHONGHUCU, SUKU DAN BISNIS ORANG-ORANG TIONGHOA DI YOGYAKARTA - , Chandra Halim; , Prof. Dr. Susetiawan ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research is aimed at describing and analyzing four problems